Honey As A Treatment For Diabetic Foot Ulcer: A Systematic Review - Insani, Ide Bagoes; Widayanti, Nurina; Rifki, Aliyya (Jurnal Plastik Rekonstruksi, 2016)
Background : Increased number of antibiotic-resistance bacteria has made honey widely reused as a modern wound treatment, including for Diabetic Foot Ulcer (DFU) treatment. Researchers have studied mean duration of wound healing and effectivity of honey dressing compared to other substances, such as povidone iodine, normal saline or alginate. This systematic review was conducted to objectively evaluate mean duration of wound healing using topical honey dressing compared to other substances in the treatment of DFU. Method : All RCT and CCT trials were collected from 4 electronic databases using keywords “Honey”, “Honey dressing”, “Diabetic foot ulcer”, and “Diabetic ulcer”. We included all English literatures with year of publication from January 2006 to November 2016; studies comparing honey with other substances; and patients with DFUs. Qualitative assessment of these studies were scored using Jadad Scale. Result : A total of 5 studies involving 517 participants were included. None of 5 studies obtained full Jadad score in quality assessment due to lack of description on randomization method, blinding and dropouts. Three studies reported significantly shorter mean duration of wound healing in honey dressing compared to normal saline and alginate dressing. Other 2 studies reported insignificant difference compared to povidone iodine, although honey still has shorter mean duration of wound healing. Two studies reported less pain during dressing changes in honey dressing group. Conclusion : Honey dressing was superior than control group (normal saline, alginate, and povidone iodine) in reducing mean duration of wound healing in DFU patients. It was also proven to cause less pain during dressing changes. Due to high heterogeneity we are unable to carry out a meta-analysis.